Direct synthesis of phosphine-phosphite ligand and its implication in asymmetric hydrogenation of functionalized olefins - Chandanshive, Amol C.; Khopade, Kishor V.; Chikkali, Samir H. (Chemistryselect, 2026)
Phosphine-phosphite (P-OP) ligands constitute a privileged class of chiral ligands in asymmetric catalysis owing to their modular structures and tunable steric and electronic properties. Herein, we report a direct, one-pot, synthesis of a new flexible P-OP ligand (L) derived from BINOL-PCl and its in situ complexation with rhodium (Rh) for catalytic evaluation. The resulting Rh/L system efficiently hydrogenates a diverse library of 19 functionalized olefins under mild conditions, delivering moderate to excellent enantioselectivities, with ee values reaching up to 99%. Several of the hydrogenated products correspond to valuable chiral building blocks relevant to pharmaceutical synthesis, underscoring the practical utility of flexible P-OP ligand architectures in asymmetric hydrogenation.
Keywords: asymmetric hydrogenation; functionalized alkene; ligand design; metal catalyzed; phosphine-phosphite